Provision of Lemon Aromatherapy for Reducing Nausea and Vomiting To Pregnant Women in First Trimester at PMB Hasnah Dewi Pekanbaru - Eka Maya Saputri (Science Midwifery, 2021)
Nausea and vomiting is a natural phenomenon and common in the first trimester of pregnancy nausea usually occurs in the morning, but can also occur at any time and night. These symptoms occur approximately after 6 weeks from the first day of the last menstrual period and last for approximately 10 weeks. In the case of Emesis gravidarum that is not treated, it will cause symptoms pathological, namely, Hyperemesis gravidarum which if left unchecked will have bad consequences later, especially in the fetus or mother's pregnancy. This study aims to determine the Effectiveness of Giving Lemon Aroma Therapy with Reducing Nausea and Vomiting in First Trimester Pregnant Women at PMB Hasnah Dewi in 2021. This type of research is a quantitative analytic study. This research was conducted at PMB Hasnah Dewi. The population in this study were all first-trimester pregnant women who visited PMB Hasnah Dewi. The sample in this study were pregnant women in the first trimester who experienced nausea and vomiting who were found in the PMB Hanah Dewi Working Area, amounting to 15 people. Based on the results of research on the effectiveness of giving citrus aromatherapy to reduce nausea and vomiting in pregnant women in the first trimester, there were 15 pregnant women who obtained the Mean Rank pretest and posttest results for the experimental group (0,0001). It is hoped that PMB Hasnah Dewi can apply lemon aromatherapy to pregnant women to help reduce nausea and vomiting experienced by pregnant women.